Kepastian Hak Perorangan dalam Proses Pendaftaran Tanah di Kecamatan Ruteng Kabupaten Manggarai - Arsenius Nggebok; Sukardan Aloysius; Petronius Damat (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The purpose of this research is to analyze the certainty of individual rights in the land registration process in Ruteng District, Manggarai Regency. In this research, empirical juridical research is used. The approach used in this research is the statute approach. The types and sources of data in this research are primary data and secondary data. Respondents in this research are the Head of Ruteng Sub-district, the Head of Meler Village, Ruteng Sub-district, and the people of Ruteng Sub-district. Data collection techniques are field study and literature study. The result of this research is that in the implementation of land registration in Ruteng Subdistrict, Manggarai Regency, in reality not all of them have been registered, especially in Meler Village, Ruteng Subdistrict, Manggarai Regency, there are 732 people who have registered their land rights out of 2,865 residents. This is due to obstacles faced by the government related to the lack of response from the community. The obstacles that occur in the process of land registration in Rureng District, Manggarai Regency include: Lack of public knowledge about the importance of land registration, Lack of public understanding of the functions and uses of certificates, Public perception that land registration is expensive, Perception that the process of obtaining certificates takes a long time, Disputes between land owners, Assumption that the basis of land rights owned is strong, Errors in the process of measuring land to be registered.